Influence of local circulations on wind, moisture, and precipitation close to Manaus City, Amazon Region, Brazil. Issue 23 (11th December 2014) - dos Santos, Mercel J.; Silva Dias, Maria A. F.; Freitas, Edmilson D.
Abstract This paper presents long‐term‐derived local wind patterns as well as their role on moisture transport and on spatial/temporal distribution of precipitation close to Manaus City region. In this analysis we used surface weather station data and rainfall estimates from TRMM (Tropical Rainfall Measuring Mission) and CMORPH (Climate Prediction Center morphing method). The weather stations promoted information of wind direction and dew point temperature, used here as atmospheric moisture indicator. The 3‐hourly average of accumulated precipitation, calculated using satellite estimates (TRMM and CMORPH), allowed to assess the spatial distribution of the rainfall diurnal cycle and how it is modulated by the local circulations. The station data results show that in the daytime, between 9:00 and 18:00 local time, winds away from the rivers are frequent, indicating action of the river breeze. This wind condition transports moist air from the rivers to the Manaus City. Winds toward rivers are commonly observed at night and in the morning, mostly at Ponta Pelada airport station, and are evidence of the land breeze occurrence. These local winds transport drier air from Manaus City to the river regions, as verified at Ponta Pelada station. The evidence of the local circulations and their impact on the moisture transport are more obvious in the dry season. The rainfall diurnal cycle has a spatial tendency varying according to the hour of the day. In the afternoon and in the evening, maximum precipitation values are observed over land, whereas reduced rainfall values are verified over rivers. At dawn and in the morning, the maximum values of accumulated precipitation are found over the rivers, mainly over and around the Amazon River. This rainfall spatial distribution is very likely modulated by local circulations and is much more evident in the rainiest quarter (March–May).